Política exterior del Ecuador frente a la agenda internacional de Energía Atómica (2007 – 2014). - Live Collantes, Tamara Leticia. (2019)
The present academic research raises a vision of the foreign policy of Ecuador framed in the Constitution of the Republic with regard to the International Atomic Energy Agenda, therefore reviews the International Atomic Energy Agency (IAEA), its origins and influence within the new "world order". The sources used in the investigation are documentary, doctrinal and legal Its conclusion raises a criticism of this new world order established from the power and hegemony and proposes to collect the political, legal and technical elements that the Ecuadorian State has, that allow to design a national political proposal for face or international energy agendas atomic and International Organizations such as the IAEA.